Social dialogue in times of crisis : finding better solutions - Rychly, Ludek (ILO GenevaCH, 2009)
Discusses the lessons that can be learnt in the sphere of industrial relations from past crises in different parts of the world. Highlights some recent industrial relations developments at the national, sectoral and enterprise levels since the beginning of the current crisis in the late summer of 2008. Suggests some preliminary policy options.